Subverting or reconceptualising professionalism? The curious case of the imposition of synthetic phonics - Deirdre Hewitt (Educational Futures)
This article links Foucault’s discussion on power and dominance with the directive to teach synthetic phonics in English schools. It would seem that teachers are being dominated by a Government power that is imposing a very narrow view of reading on all teachers, students and thus on children. Compliance and accountability now reign supreme in the world of the University and in the classroom. When exploring the theme of power Foucault refers to a ‘game of truth’. This raises the question: is this what teachers are reduced to, playing a game? The game it seems must be played in order to appease the ‘inspecting gaze’ (Foucault 1977) of the Government. The article by employing the metaphor of the battle and of the Pentecost – where people were blessed them with the ‘gift of tongues’ – explores how notions of professionalism are reconceptualised or even subverted within the context of ‘playing the accountability game’.